THE INFLUENCE OF SELF-CONFIDENCE, READINESS TO LEARN, PEERS AND FAMILY ENVIRONMENT ON THE LEARNING ACHIEVEMENT OF CLASS X STUDENTS IN SUBJECTS ECONOMICS THROUGH LEARNING DISCIPLINES VARIABLE INTERVENTION AS AT PERTIWI 1 SMA - Humairah, Siti; Yasmi, Fifi; Stevani (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine the influence of self-confidence, learning readiness, peers, and family environment on learning discipline. It also aims to determine the influence of self-confidence, learning readiness, peers, family environment, and learning discipline on academic achievement. This type of research is descriptive and associative. The population in this study consisted of 131 students of class X at SMA Pertiwi 1 Padang. The sample was taken using a stratified random sampling technique. The instruments used in this study were closed questionnaires, and the analysis tests used included path analysis, hypothesis testing, and t-tests, with the assistance of SPSS and Eview8 programs. The results of this study are: 1) there is an effect of self-confidence on learning discipline with a coefficient value of 0.371 and a t-count value of 2.897 > t-table 1.666, 2) there is an effect of learning readiness on learning discipline with a coefficient value of 0.438 and a t-count value of 4.552 > t-table 1.666, 3) there is an effect of peers on learning discipline with a coefficient value of 0.258 and a t-count value of 2.737 > t-table 1.666, 4) there is no effect of family environment on learning discipline with a coefficient value of -0.143 and a t-count value of -1.913 > t-table 1.666, 5) there is an effect of self-confidence on learning achievement with a coefficient value of 0.190 and a t-count value of 2.047 > t-table 1.666, 7) There is an influence of peer groups on learning achievement with a coefficient value of 0.467 and a t-count value of 5.845 > t-table 1.666, 8) there is an influence of family environment on learning achievement with a coefficient value of -0.419 and a t-count value of 6.802 > t-table 1.666, 9) there is an influence of learning discipline on learning achievement with a coefficient value of 0.205 and a t-count value of 2.147 > t-table 1.666.